Ilmenite: A promising oxygen carrier for the scale-up of chemical looping. (1st April 2023) - Bartocci, Pietro; Abad, Alberto; Flores, Arturo Cabello; de las Obras Loscertales, Margarita
Graphical abstract: Highlights: The paper presents a review on the application of ilmenite in CLC, CLR and CLOU. Calcination increase ilmenite reactivity and OTC. Ilmenite has good reactivity with syngas. Ilmenite reactivity with methane is lower respect to other oxygen carriers. Cost of OC makeup for unit of energy released by the FR is a key economic index. Abstract: To tackle the scale-up of Chemical Looping Processes, the production of efficient and affordable oxygen carriers appears of paramount importance. Ilmenite is an ore-derived oxygen carrier which can be considered surely abundant and cheap. The preparation and the characterization of its reactivity are presented in the following paper. The paper describes briefly the performance of ilmenite relating it to other oxygen carriers, its thermodynamic properties, the kinetics and its use with fuels (solid, liquid and gaseous, including biofuels). Key features for an oxygen carrier are represented by costs and environmental sustainability, oxygen transport capacity and reactivity, as well as specific issues related to its use in fluidized bed reactors, namely agglomeration and attrition behavior. In addition, information about mutual interaction with fuel, considering also the influence of impurities, coke deposition or its effect on the gasification rate of solid fuels, is reported.